Effect of the nitrogen source on the hydrogen production metabolism and hydrogenases of Clostridium butyricum CWBI1009. (15th March 2018) - Hamilton, Christopher; Calusinska, Magdalena; Baptiste, Stacy; Masset, Julien; Beckers, Laurent; Thonart, Philippe; Hiligsmann, Serge
Abstract: Investigations were carried out to determine the effect of various concentrations of organic and ammonium nitrogen sources on fermentative hydrogen production by the strain Clostridium butyricum CWBI1009. The results indicated that the H2 -producing metabolism of the strain is favoured within the range (0.56–0.062 gN /L) of peptone and (NH4 )2 SO4 . Optimal overall performance ( i.e. 1.43 ± 0.08 mol H2 /mol glucose and 1.08 ± 0.03 mLH2 /h, respectively) was achieved with 0.062 gN /L of casein peptone. The study of the amino acid uptake and the gene expression pattern for four [FeFe]-hydrogenases and the nitrogenase showed that nitrogen was in excess in all the experiments with a nitrogen concentration above 0.062 gN /L and, at that optimal concentration, the expression of the HydB2 gene would be responsible for the much higher H2 yield. Highlights: Effect of nitrogen sources was studied on Clostridium biohydrogen production. Four organic or ammonium nitrogen sources and ten concentrations were tested. Optimal overall performance was achieved with 0.062 gN /L of casein peptone. H2 production yield and rate peaked at 1.43 molH2 /molglucose and 1.08 mLH2 /h. Amino acid distribution and hydrogenase expression were investigated.